Tau Phosphorylation, Aggregation, and Cell Toxicity. (3rd January 2006) - Avila, J.; Santa-María, I.; Pérez, M.; Hernández, F.; Moreno, F.
Abstract : Protein aggregation takes place in many neurodegenerative disorders. However, there is a controversy about the possible toxicity of these protein aggregates. In this review, this controversy is discussed, focussing on the tau aggregation that takes place in those disorders known as tauopathies.